Baseline characteristics of systemic lupus erythematosus patients included in the Lupus Italian Registry of the Italian Society for Rheumatology. (July 2021) - Sebastiani, Gian Domenico; Spinelli, Francesca Romana; Bartoloni, Elena; Bortoluzzi, Alessandra; Bozzolo, Enrica; Canofari, Claudia; Canti, Valentina; Conigliaro, Paola; Ditto, Maria Chiara; Emmi, Giacomo; Franceschini, Franco; Frassi, Micol; et al.
Objective: To report baseline data of SLE patients enrolled in the Lupus Italian Registry (LIRE). Methods: Patients affected by SLE aged ≥ 16 years were consecutively recruited in a multicenter prospective study comparing two cohorts: patients starting biologic immunosuppressants (BC) and patients starting non-biologic immunosuppresants (NBC). Results: 308 patients were enrolled, 179 in NBC and 129 in BC. Mean age at disease onset and at diagnosis was significantly higher in NBC (p = 0.023, p = 0.045, respectively). Disease duration was longer in BC (p = 0.022). Patients in BC presented arthritis more frequently (p = 0.024), those in NBC nephropathy (p = 0.03). Quality of life was worse in BC (p = 0.031). Anti-dsDNA, low C3, were significantly more frequent in BC (p < 0.001, p = 0.009, respectively). Mycophenolate, methotrexate and azathioprine were the drugs more frequently prescribed in NBC, Belimumab and Rituximab in BC. Conclusion: The predominant organ involvement was different in the two cohorts: kidney involvement predominated in NBC, joint involvement in BC. Despite the younger age at disease onset, patients of the BC had a longer disease duration and more frequently had taken a cumulative prednisone dosage greater than 10 g. Even the pattern of clinical manifestations inducing to prescribe biological rather than conventional immunosuppressants was quite different. Keywords: Autoantibody(ies), autoimmune disease, belimumab, cohort studies, glucocorticoids, immunosuppressants, rituximab, systemic lupus erythematosus